2017
DOI: 10.1002/rev3.3099
|View full text |Cite
|
Sign up to set email alerts
|

Educating young adults to be work‐ready in Ireland and the United Kingdom: A review of programmes and outcomes

Abstract: Across Europe, young adult unemployment remains an important issue. Those who have grown up in contexts of social and educational disadvantage can find it particularly difficult to find work. In response, governments, charitable foundations and in the rare case, researchers, have developed programmes of training and work‐based learning to help them enter the workforce. These programmes aim to improve the young adults’ work‐readiness (also known as work‐preparedness or career‐readiness), which can be viewed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Moreover, in line with a human capital approach (Hamilton et al, 2013;Hutchinson et al, 2016;Symonds & O'Sullivan, 2017), the findings from this thesis showed that work-based placements, volunteering experiences, and mock interview events can support disengaged young people in navigating the transition to employment by developing their work-readiness competencies and employability skills (e.g., self-awareness, communication, leadership, and problem-solving skills).…”
Section: How Did the Multi-component Programmes Work For Whom And Under Which Circumstances?supporting
confidence: 58%
See 2 more Smart Citations
“…Moreover, in line with a human capital approach (Hamilton et al, 2013;Hutchinson et al, 2016;Symonds & O'Sullivan, 2017), the findings from this thesis showed that work-based placements, volunteering experiences, and mock interview events can support disengaged young people in navigating the transition to employment by developing their work-readiness competencies and employability skills (e.g., self-awareness, communication, leadership, and problem-solving skills).…”
Section: How Did the Multi-component Programmes Work For Whom And Under Which Circumstances?supporting
confidence: 58%
“…Moreover, through engagement with a range of occupations, it was apparent that many young people in EMPOWER developed new skills and competencies, including, communication, leadership, and problem-solving skills. These findings can be interpreted within the human capital approach (Hamilton et al, 2013), which highlights that effective reengagement programmes help young people to develop and improve their workreadiness competencies in order to prepare them for employment and/or educational opportunities after programme completion (Symonds & O'Sullivan, 2017).…”
Section: Initial Programme Theory 4: the Importance Of A Youth-driven Multi-component Programmementioning
confidence: 97%
See 1 more Smart Citation
“…Regarding countries with the highest percentage of articles in these years, the UK has more than 48.0% of the total publications, followed by Australia (15.1%) and the US (11.0%). This expressive number may relate to the use of WBL in the UK and other English-speaking countries for more than 30 years at higher education level (Stern, 1999;Wearne et al, 2015;Symonds and O'sullivan, 2017;Talbot et al, 2017b;Talbot et al, 2017a;Hardwick-Franco, 2018). However, it is noteworthy a predominance of European countries generating and publishing knowledge on WBL (Jansen and Pineda-Herrero, 2019;Loos, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Whilst interpreting the NEET category in this way increases its diversity and reduces its meaning and explanatory power, it can be understood as part of a broader ideological shift whereby structural unemployment has been recast as a problem of individual participation (Simmons and Thompson 2011). However, the practical outcome of this shift is that poorly-qualified working-class youth have particularly unattractive options: competing with older workers, usually for low-quality employment, or receiving benefits conditional on attending 'employability' programmes which rarely help them find sustained employment (Symonds and O'Sullivan 2017).…”
Section: Neet -The Rise Of a Problem Categorymentioning
confidence: 99%